Bulletin on food price dynamics, inflation and the food security situation in Sudan: November-December 2022 - Ahmed, Mosab O. M.; Siddig, Khalid (International Food Policy Research Institute, 2023)
Highlights: • The decline in international prices, especially for food commodities, helped to limit overall price inflation in Sudan in November and December 2022. Consequently, the annual inflation rates in these months were lower than the inflation rate in October 2022. • Local prices of some food commodities noticeably decreased in November 2022 compared to October 2022, especially for cereals (wheat, millet, and sorghum). This decline continued in December 2022. • Local prices of internationally traded food commodities were affected by the fluctuations in the exchange rate during December 2021 to December 2022. • Higher inflation rates are observed in relatively unstable states (in urban and rural areas) compared to the national average. • The monthly inflation rate of food and beverages decreased to 59 percent in November from 70 percent in October 2022 driven by the declining CPI for the bread and cereals group.